Nitric oxide regulates adhesiveness, invasiveness, and migration of anoikis-resistant endothelial cells - Mesquita,A.P.S. (2022)
Anoikis is a type of apoptosis that occurs in response to the loss of adhesion to the extracellular matrix (ECM). Anoikis resistance is a critical mechanism in cancer and contributes to tumor metastasis. Nitric oxide (NO) is frequently upregulated in the tumor area and is considered an important player in cancer metastasis. The aim of this study was to evaluate the effect of NO on adhesiveness, invasiveness, and migration of anoikis-resistant endothelial cells. Here, we report that anoikis-resistant endothelial cells overexpress endothelial nitric oxide synthase. The inhibition of NO release in anoikis-resistant endothelial cells was able to decrease adhesiveness to fibronectin, laminin, and collagen IV. This was accompanied by an increase in cell invasiveness and migration. Furthermore, anoikis-resistant cell lines displayed a decrease in fibronectin and collagen IV protein expression after L-NAME treatment. These alterations in adhesiveness and invasiveness were the consequence of MMP-2 up-regulation observed after NO release inhibition. The decrease in NO levels was able to down-regulate the activating transcription factor 3 (ATF3) protein expression. ATF3 represses MMP-2 gene expression by antagonizing p53-dependent trans-activation of the MMP-2 promoter. We speculate that the increased release of NO by anoikis-resistant endothelial cells acted as a response to restrict the MMP-2 action, interfering in MMP-2 gene expression via ATF3 regulation. The up-regulation of nitric oxide by anoikis-resistant endothelial cells is an important response to restrict tumorigenic behavior. Without this mechanism, invasiveness and migration potential would be even higher, as shown after L-NAME treatment.